Analýza platební bilance - Kovářová, Lucie (Univerzita Pardubice, 2006)
Práce se zabývá teoretickým vymezením pojmu, struktury a jednotlivých sald platební bilance. Ve druhé části stručně popisuje vývoj a determinanty vývoje jednotlivých účtů platební bilance České republiky v letech 1997 – 2004.

The bachelor work with the title ‘‘The Analysis of Balance of Payments ” is dealing with the term balance of payments, horizontal and vertical structure of balance of payments and the particular balances of payments.The second part of the work is dealing with the evolution of the balance of payments of the Czech Republic in the years 1997 - 2004 and main determinants of its creation in particular years.
The analysis of balance of payments
Keywords: Balance of payments; current accounts; balance of trades; financial accounts; foreign exchange reserves; foreign indebtedness of the Czech Republic; Platební bilance; běžné účty; obchodní bilance; finanční účty; devizové rezervy; zahraniční zadluženost ČR